Cochrane Database of Systematic Reviews 2008
DOI: 10.1002/14651858.cd005284.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for peritoneal dialysis-associated peritonitis

Abstract: Analysis 1.2. Comparison 1 Intravenous (IV) versus intraperitoneal (IP) antibiotics, Outcome 2 Adverse events.. . Analysis 1.3. Comparison 1 Intravenous (IV) versus intraperitoneal (IP) antibiotics, Outcome 3 Infusion pain.. . Analysis 2.1. Comparison 2 Oral (drug A) versus intraperitoneal (drug A) antibiotics (same antibiotic), Outcome

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 79 publications
1
18
0
3
Order By: Relevance
“…administration of antibiotics is superior to i.v. dosing (12). As expected, we detected a prolonged half-life in serum compared to that in patients with intact renal function (5).…”
supporting
confidence: 80%
“…administration of antibiotics is superior to i.v. dosing (12). As expected, we detected a prolonged half-life in serum compared to that in patients with intact renal function (5).…”
supporting
confidence: 80%
“…For example, many patients practice peritoneal dialysis-peritonitis and intraperitoneal administration of antibiotics. This is superior to other intravenous therapies [20] and allows ongoing outpatient treatment, which shortens hospital admission which is beneficial to both patients and to health care system [1]. Therefore, reliable and widely available stability information of antibiotics in the Accufuser ® infusion device is clinically important.…”
Section: Discussionmentioning
confidence: 99%
“…Several controlled and uncontrolled studies with widely var ying inclusion criteria and procedural protocols have assessed the efficacy of fibrinolytic agents in resolving resistant and preventing recurrent infections (236)(237)(238)(239)(240)(241)(242)(243). A placebo-controlled trial showed no significant effect of urokinase when administered intraperitoneally (30 000 IU/L) as adjuvant therapy in antibiotic-resistant bacterial peritonitis (242).…”
Section: Guideline 153mentioning
confidence: 99%
“…Catheter exchange has been shown to be superior to urokinase in lowering treatment failure rates in relapsing or persistent peritonitis (237,243). Not surprisingly, that finding is especially true with respect to relapsing peritonitis related to a TI or intra-abdominal abscess, which always should be carefully ruled out in patients with relapsing peritonitis.…”
Section: Guideline 154mentioning
confidence: 99%
See 1 more Smart Citation